Bioviolence Preventing Biological Terror and Crime - Kellman, Barry (Cambridge University Press, 2013)
As this book is written, civil war and insurgency inflame Iraq; Palestinians and Israelis unrelentingly clash; and genocide perpetuates in Darfur. With time, other and perhaps worse conflicts will come to the fore. Eventually, some combatant or fanatic will choose to raise the stakes by using a weapon that altogether multiplies casualties. Just as planes flying into towers on 9/11 instantly became an historical marker dividing strategic perspectives before from after, that day will herald the onslaught of disease as an instrument of malevolence, profoundly changing everything.